Quem são os povos indígenas para os estudantes? Reflexões sobre o currículo básico comum do estado de Minas Gerais - Gilaverte, Ana Paula (2014)
The indigenous issue presented in the school context on the view of European blueprints may generate numerous misconceptions, reflecting attitudes of prejudice, rejection, discrimination and segregation. Although they represent a group of ethnic-cultural formation of Brazil, their history remains overlooked, covered in the school context as mere individuals from the time of contact with the Europeans, leaving a deep gap regarding the participation of those groups throughout the history of Brazil. Thus, a perspective that is intended to be multicultural and interactive should bring the debate to the classroom on diversity and difference as being dynamic, fluid, and ever-changing processes. Issues that pervade historic school discourses and similar ones, influence the construction process of individual and collective identification of the student. In this research, we aim to draw considerations on school discourses related to indigenous people, and on how the student builds his identification toward those groups, from the discourses that are recognized, accepted, and instituted in the matrix of the Common Basic Curriculum of Minas Gerais, in the subject of history. These perceptions point to an approach based on speeches that gained tradition throughout the history of Brazil, having the European discourse as its core.